2018
DOI: 10.1021/acs.est.7b05982
|View full text |Cite
|
Sign up to set email alerts
|

Particle/Gas Partitioning of Phthalates to Organic and Inorganic Airborne Particles in the Indoor Environment

Abstract: The particle/gas partition coefficient K is an important parameter affecting the fate and transport of indoor semivolatile organic compounds (SVOCs) and resulting human exposure. Unfortunately, experimental measurements of K exist almost exclusively for atmospheric polycyclic aromatic hydrocarbons, with very few studies focusing on SVOCs that occur in indoor environments. A specially designed tube chamber operating in the laminar flow regime was developed to measure K of the plasticizer di-2-ethylhexyl phthala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 42 publications
2
41
1
Order By: Relevance
“…19 Chamber studies of organophosphate flame retardants and plasticizers have demonstrated similar partitioning phenomena whereby the presence of airborne particles enhances the rate of SVOC emissions from source materials. [20][21][22] Moreover, the affinity of SVOCs for airborne particles is affected by both SVOC and particle composition for phthalate diesters 22,23 and for third-hand smoke (THS) species. 24 These findings have been supported by measurements in real indoor environments for specific compounds.…”
Section: Introductionmentioning
confidence: 99%
“…19 Chamber studies of organophosphate flame retardants and plasticizers have demonstrated similar partitioning phenomena whereby the presence of airborne particles enhances the rate of SVOC emissions from source materials. [20][21][22] Moreover, the affinity of SVOCs for airborne particles is affected by both SVOC and particle composition for phthalate diesters 22,23 and for third-hand smoke (THS) species. 24 These findings have been supported by measurements in real indoor environments for specific compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Theory as well as laboratory‐controlled studies predict increased emissions from indoor sources (eg, building materials) to indoor air at elevated temperatures . In addition, model simulation and chamber studies on specific SVOCs have shown that enhanced particle mass loading could facilitate partitioning of gaseous SVOCs in airborne particles, thus altering the SVOC distribution and exposure . Until now, however, no studies have documented the influence of temperature and particle mass loading on the indoor air SVOC concentrations in real indoor environments under normal occupancy, thus restricting efforts to validate models for indoor environmental emissions, fates, and gas/particle distributions of SVOCs and associated human exposures …”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35] In addition, model simulation and chamber studies on specific SVOCs have shown that enhanced particle mass loading could facilitate partitioning of gaseous SVOCs in airborne particles, thus altering the SVOC distribution and exposure. [36][37][38][39] Until now, however, no studies have documented the influence of temperature and particle mass loading on the indoor air SVOC concentrations in real indoor environments under normal occupancy, thus restricting efforts to validate models for indoor environmental emissions, fates, and gas/particle distributions of SVOCs and associated human exposures. 35,36,40,41 Furthermore, the influence of human occupants on the dynamic behavior and chemical composition of SVOCs indoors remains poorly characterized.…”
mentioning
confidence: 99%
“…52 Recent experiments by Wu et al found DEHP particle/gas partition coefficients are higher in the presence of organic particles (squalane and oleic acid) than in the presence of inorganic particles (ammonium sulfate). 53 Weschler and Nazaroff described an equilibrium model of indoor SVOC partitioning between the gas phase and settled dust using the octanol-air partitioning coefficient (K oa ); that model can also be applied to airborne particles. 49 In Equation 1, the particle-gas partition coefficient, K p , is determined where f om_part refers to the volume fraction of organic matter in airborne particles, and ρ part refers to the density of particles.…”
Section: Introductionmentioning
confidence: 99%